2007
DOI: 10.1080/10428190701528509
|View full text |Cite
|
Sign up to set email alerts
|

Primary salivary gland lymphoma among Japanese: A clinicopathological study of 30 cases

Abstract: To clarify the clinicopathological findings of primary salivary gland lymphoma as defined by the World Health Organization (WHO) classification, 30 Japanese patients with this disease were studied. The male to female ratio was 1:1.7 and median patient age was 57 years. The parotid gland (n = 22) was involved most frequently, followed by the submandibular gland (n = 5) and minor salivary gland (n = 3). Twenty-four (80%) cases demonstrated Stage IE, whereas only six (20%) had Stage IIE-1. None of the 30 cases ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 24 publications
8
38
0
Order By: Relevance
“…This is in keeping with other studies that have reported a rate of 8-46 % of primary SG MALT-L patients with Sjogren's syndrome [10][11][12][13]. None of our lesions were bilateral.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is in keeping with other studies that have reported a rate of 8-46 % of primary SG MALT-L patients with Sjogren's syndrome [10][11][12][13]. None of our lesions were bilateral.…”
Section: Discussionsupporting
confidence: 93%
“…Within the limited literature, there is some variability in the reported histological distribution of primary SG lymphomas (Table 3), but on the whole, low grade B-cell lymphomas predominate [10-13, 27, 28]. The majority of SG lymphomas are reported to originate in the parotid gland, which is consistent with our results [2,7,12,29]. As expected, all our primary lymphomas were B-cell lymphomas.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…[1][2][3][4] However, there are only limited data available on the prognostic impact of various sites of extralymphatic involvement in the rituximab era, 5,6 and none from patients exclusively treated within prospective trials. 5,[7][8][9][10][11][12][13][14] An increased risk of central nervous system (CNS) disease has been reported for DLBCL of the paranasal sinuses, but not for other sites of extralymphatic craniofacial involvement (E CFI ), 9,10 and combined chemoradiotherapy has been recommended for these sites. 14 We now report the results of an analysis of 11 consecutive trials of the German High-Grade Non-Hodgkin Lymphoma Study Group (DSHNHL), describe clinical characteristics, and identify factors that affect the outcome of patients with E CFI treated with and without rituximab.…”
Section: Introductionmentioning
confidence: 99%